Peran Daya Tarik Desa Wisata dan Community Based Tourism dalam Membangun Citra Desa Wisata - Syarif Hidayatullah; Irany Windhyastiti; Abdul Waris; Irany Windhyastiti (University of Merdeka Malang, 2021)
This study aims to determine: 1) the influence of tourist village attraction to image of tourist village; 2) the influence of community based tourism to image of tourist village; and 3) the influence of community based tourism in strengthening tourist village attraction to images of tourist village. This research was conducted in Batu City with a sample of 120 tourists. The results show: 1) the tourist village attraction has a significant effect to images of tourist village; 2) the influence of community based tourism has a significant effect to images of tourist village; and 3) the community based tourism does not strengthen the influence of tourist village attraction to images of tourist village, but the direct influence of Community Based Tourism on the image of a tourist village is greater than the direct effect of the attractiveness of a tourist village on the image of a tourist village